Health psychology - TAYLOR, Shelley E. (New York, NY : McGraw-Hill, 2012)
"The eighth edition of Health Psychology highlights health issues that face the college student and his or her family through both accessible research examples and profiles of interventions. It also highlights health issues relevant to the college students immediate and global environment with both accessible research examples and profiles of interventions. This edition contains clear descriptions on current research into the prevention, treatment, and causes (social, genetic, and biological) of health related disorders"--
Includes bibliographical references (p. 405-486) and index.
Keywords: Clinical health psychology; Medicine, Psychosomatic; PSYCHOLOGY / General